2019
DOI: 10.1140/epjc/s10052-019-6976-0
|View full text |Cite
|
Sign up to set email alerts
|

Coupled-channel-induced $$S{-}D$$ mixing of Charmonia and testing possible assignments for Y(4260) and Y(4360)

Abstract: The mass spectrum and the two-body opencharm decays of the J PC = 1 −− charmonium states are studied with the coupled-channel effects taken into account. The coupled-channel-induced mixing effects among the excited vector charmonia are studied. Based on our calculations of the masses and the decay widths, we find that the tension between the observed properties of Y (4260)/Y (4360) and their conventional charmonia interpretations could be softened.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 57 publications
1
18
0
Order By: Relevance
“…However, the application of epoxy resins is restricted by their inherent brittleness. To eliminate this drawback, different tougheners, including rubbers, glass particles and engineering thermoplastics [9][10][11][12], have been used to modify epoxy resins. However, these modifications often cause the deterioration of processing performance, glass transition temperature (T g ) and mechanical properties of epoxy resins.…”
Section: Introductionmentioning
confidence: 99%
“…However, the application of epoxy resins is restricted by their inherent brittleness. To eliminate this drawback, different tougheners, including rubbers, glass particles and engineering thermoplastics [9][10][11][12], have been used to modify epoxy resins. However, these modifications often cause the deterioration of processing performance, glass transition temperature (T g ) and mechanical properties of epoxy resins.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] In scanning tunneling spectroscopy (STS) experiments,t he presence of an unpaired electron can be detected through the measurement of the Kondo resonance, originating from the interaction between the unpaired electron spin localized on the molecule and the conduction electrons of an onmagnetic substrate. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] In scanning tunneling spectroscopy (STS) experiments,t he presence of an unpaired electron can be detected through the measurement of the Kondo resonance, originating from the interaction between the unpaired electron spin localized on the molecule and the conduction electrons of an onmagnetic substrate.…”
mentioning
confidence: 99%
“…By using differential scanning calorimetry, it was confirmed that the Curie temperature, T C , of Ba 1Àx Ca x TiO 3 was above 369 K, which is consistent with previous studies. [25,27,28] A typical heat capacity of Ba 1Àx Ca x TiO 3 was approximately 0.16 J K À1 . The electric displacement, D, of the square-plate samples was measured by the varying electric field, E, at room temperature by means of the double-wave method.…”
Section: Methodsmentioning
confidence: 99%